Photochemically Mediated Toluene Oxidation through a Copper Complex - Noß, Christian; Göttlich, Richard; Schindler, Siegfried; Justus Liebig University Giessen (My University, 2023)
A method is described to photochemically oxidize toluene selectively to benzaldehyde, an essential compound in the chemical industry. Copper(I) complexes with different ligands were applied in combination with [Ru(bipy)3](PF6)2 and dioxygen as the oxidant. As a result, a “dioxygen adduct” copper complex, for example, a peroxido complex, is formed as the active species. The copper(II) complex obtained after oxidation can be photochemically reduced to the starting copper(I) species, and the process can be repeated continuously. The ligand tris(2-methylpyridyl)amine (tmpa) led to the highest conversion rates.
Keywords: copper peroxido complexes; photooxidation; benzaldehyde; toluene oxidation; ruthenium bipyridine; ddc:540